A novel antibacterial compound from an untapped plant: Stereospermum fimbriatum - Sarker, Md. Zaidul Islam; Awang, Anis Fadhlina Izyani; Ahmed, Qamar Uddin; Md. Jaffri, Juliana (2019)
Background: Stereospermum fimbriatum or locally known as “Chicha” is traditionally used for itchy skin, earache, stomachache and postpartum treatments. Objective: This study was designed to evaluate the antimicrobial potential of S. fimbriatum’s stem bark against 11 pathogens and isolate its bioactive compound. Material and methods: Successive soxhlet extraction was conducted using n-hexane, dichloromethane (DCM) and methanol. Disc diffusion, minimum inhibitory and bactericidal concentration (MIC & MBC) assays were done to examine the antimicrobial activity. Bioassay-guided isolation was conducted on S. fimbriatum’s extract. Results: The DCM extract of stem bark (DS) was the most potent extract followed by n-hexane extract of the stem bark (NS). A novel compound was isolated and coded as C1 which demonstrated potent antibacterial effects with the MIC values as low as 3.13 μg/mL to 6.25 μg/mL, against S. epidermidis, MRSA and S. aureus. Conclusion: S. fimbriatum could be a potential source of antimicrobial agents for the treatment of skin infections, specifically, MRSA.